(untitled) (Journal on studies and research of academic knowledge, 2017)
Visual characteristics and incidence of fungi associated with rice spotted grainswere determined by seed health testing using the blotter method. For each sample, 400seeds were placed in petri dishes with three moistened filters and incubated for 8 days with12 hourslight/darkness at 22-25° C. Taxonomic and manual identification codes were used for the determination of genera and species. Identification and incidence of ten fungal generapresent in rice-spotted grains were determined: Alternariapadwickii Bipolarisoryzae; Curvularia lunata; Curvulariaspp; Fusariumspp; Phomaspp; Exserohilumspp; Nigrosporaspp, Alternariaspp and Pyriculariagrisea. Alternariapadwickii was the specie with the highest incidence of rice spotted fungi.